Insights from electron backscatter diffraction into the origin of fibrous calcite veins in organic-rich shale from lower Es3 to upper Es4, Jiyang Depression, China. (March 2020) - Ma, Cunfei; Dong, Chunmei; Elsworth, Derek; Wang, Qian; Huang, Zhi; Liu, Hailei; Luan, Guoqiang; Yu, Baojun; Li, Dan; Yin, He; Feng, Meng; He, Yueming
Abstract: The origin of fibrous calcite veins developed in organic-rich shales, has attracted great attentions. However the growth direction, formation temperature and stress state are still controversial. The calcite veins in organic-rich shale from lower Es3 to upper Es4 in the Jiyang Depression has been analyzed with electron backscatter diffraction technology (EBSD), which can characterize the microstructures and orientation of mineral crystals in situ. On the basis of core observation and microscopic identification of petrological characteristics, the longitudinal and horizontal profiles of calcite veins were measured by EBSD. Crystallographic information on calcite veins, obtained by pattern quality mapping, phase diagrams, grain distribution maps, Euler graphs, grain misorientations and pole figures, clarifies the origins of these veins. The results show that calcite crystals in calcite veins belong to the sharp-rhombohedral space lattice structure of the trigonal system. Calcite crystals have a preferred orientation on the longitudinal profile, while there is no obvious preferred orientation on the horizontal profile. On the longitudinal profile of calcite veins, the misorientation of calcite crystals is the cause of the interference colour and extinction difference of calcite crystals under orthogonal light. The crystal interference and extinction characteristics on both sides of middle line in calcite veins are different, indicating that the growth direction of calcite veins is syntaxial. A shallow burial environment is suggested for calcite veins initial forming by the evidence that crystal morphology of calcite in calcite veins is most in the shape of sharp-rhombohedron, and some of which have hexagonal prism shape. The average orientation difference of calcite veins on longitudinal and horizontal profiles indicates that the average orientation of calcite grains is inhomogeneous. The stress concentration of small grains is higher than that of large grains, and cracks are developed in the interior or on the border of calcite grains on the longitudinal profile, which indicates that calcite veins are formed in the stress environment of three directional extrusion circumstances. Highlights: Electron backscatter diffraction technique can be well used to characterize the crystal habit of fibrous calcite veins. Calcite crystals in fibrous calcite veins belong to the sharp-rhombohedral space lattice structure of trigonal system. Calcite veins are formed under the condition of low temperature and three-dimensional compressive stress.